USE OF MIND MAPPING METHOD IN LEARNING WRITING TEXT EXPLANATION - Suci Rizkiana; Suryo Ediyono (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract : The purpose of this study was to determine the increase in interest and writing skill of explanation text using mind mapping method in students of Nusawungu State Vocational School. This research is a classroom action research conducted in two cycles. Research subjects were students and teacher of Indonesian language class at grade  XI. Data sources in this study included: learning events, informants, and documents. Data collection technique through: observation, interviews, tests, and document analysis. Validity test of the data used  triangulation techniques and data source methods. Data analysis techniques used in this study were comparative descriptive techniques and critical analysis. The use of mind maping method was proven to increase students' interest in learning to write explanatory texts. The percentage of students' interest in pre-cycle was 52.94%, cycle I was 67.64%, and cycle II was 88.24%. The use of mind mapping method has also succeeded in improving writing skill of explanation text. This can be seen from the average score obtained by students. In pre-cycle, the average score of students is only 65.79. In cycle I it became 74. In cycle II, the average score of students became 79.79. Based on these results it can be concluded that the use of mind mapping methods can improve the process and learning outcomes of students in writing explanatio texts. Keywords : Mind Mapping Method, Learning, Explanatory Text.Abstrak : Tujuan  penelitian  ini  adalah  untuk mengetahui peningkatan  minat dan keterampilan menulis teks eksplanasi menggunakan metode mind mapping pada  siswa  kelas  XI SMK Negeri Nusawungu. Penelitian  ini merupakan  penelitian  tindakan  kelas  yang  dilaksanakan  dalam dua siklus.  Subjek penelitian adalah siswa dan guru bahasa Indonesia kelas XI SMK Negeri Nusawungu. Sumber  data  dalam  penelitian  ini  meliputi: peristiwa pembelajaran,  informan, dan dokumen. Teknik pengumpulan data melalui: observasi,  wawancara,  tes,  dan  analisis  dokumen.  Uji  validitas  data  menggunakan teknik  triangulasi  metode  dan  sumber  data.  Teknik  analisis  data  yang  digunakan dalam penelitian ini adalah teknik deskriptif komparatif dan analisis kritis. Penggunaan metode mind maping terbukti  dapat  meningkatkan minat siswa dalam pembelajaran menulis teks eksplanasi.  Persentase minat siswa pada prasiklus sebesar 52,94%, siklus I sebesar 67,64%, dan siklus II sebesar 88,24%. Penggunaan metode mind mapping juga berhasil meningkatkan keterampilan menulis teks eksplanasi. Hal ini terlihat dari nilai rata-rata yang diperoleh siswa. Pada prasiklus, nilai rata-rata siswa hanya 65,79. Pada siklus I menjadi 74. Pada siklus II, nilai rata-rata siswa menjadi 79,79. Berdasarkan hasil tersebut dapat disimpulkan bahwa penggunaan metode mind mapping dapat meningkatkan proses dan hasil pembelajaran menulis teks eksplanasi siswa.Kata kunci: Metode Mind Mapping, Pembelajaran, Teks Eksplanasi.